QUASI-LEGAL EFFECTS OF THE LAW NO. 05/L-079 ON STRATEGIC INVESTMENTS OF THE PROVISIONAL INSTITUTIONS OF SELF-GOVERNMENT OF AUTONOMOUS PROVINCE KOSOVO AND METOHIJA - Miljković, Strahinja D.; Simić, Igor (Zbornik radova Pravnog fakulteta u Nišu, 2020)
With the adoption of Resolution 1244, the United Nations Interim Administration (UNMIK) gains the status of guardian of state and social property R.  Serbia in the territory of the AP of Kosovo and Metohija.  For the purpose of the paper, the author pays special attention to certain regulations issued by the UNMIK administration that formed the basis for the creation of a quasi-legal system in the area of ​​the AP of Kosovo and Metohija. However, by adopting Regulations with the force of law, UNMIK or the Special Representative unilaterally abrogates the retroactively existing legal system, creating conditions for the establishment of a quasi-legal system independent of the legal system of R.  Serbia.  UNMIK/REG/1999/24 results in the reincarnation of SFRY-era legal acts.  Regulation no.  1999/24 is a guideline in further legal normalization and design of a quasi-legal system in the area of the AP of Kosovo and Metohija.  For the purpose of the paper, the author also pays special attention to the Law on Strategic Investments adopted by the Provisional Institutions of of Self-Government the AP of Kosovo and Metohija.  The significance of the said law is that it represents another in a series of acts that results in changes in the property and legal regime of state and social property (immovable property).  However, full implementation of the law became possible at the time of the adoption of Decision no.  06/134.  By decision no.  06/134 allows all real estate registered in the name of the Socialist Federal Republic of Yugoslavia or the Republic of Yugoslavia, the Socialist Republic of Serbia, that is, the Republic of Serbia and the Socialist Autonomous Province of Kosovo to be registered at the PISG of Kosovo and Metohija as the owner of the immovable .  Key words:UNMIK, Regulation, quasi-legal system, Law on Strategic Investments, Decision, Strategic Investment, Provisional Institutions of of Self-Government, immovable property.